Spatial distribution of the proteome in the human body and in cancers - Liang Yue; Wenhao Jiang; Sainan Li; Meng Luo; Ning Fan; Xiaolu Zhan; Rui Sun; Honghan Cheng; Zhangzhi Xue; Tong Liu; Qianhe Zhou; Kexin Chen; et al. (Nature, 2026)
Abstract A detailed, spatially resolved quantitative map of the human proteome is essential for a deeper understanding of human biology and disease 1–4 . Here we present a comprehensive human proteomic landscape, generated by profiling more than 13,000 proteins across 2,856 samples using data-independent acquisition mass spectrometry. The dataset spans 58 major tissue types, 251 specific tissue subtypes and 25 distinct carcinomas. This resource enables the depiction of spatially resolved proteome trajectories across tissue types and physiological states, including fetal, tumour, adjacent non-tumour and healthy adult tissue, thereby providing insight into both developmental processes and oncogenic progression. Furthermore, quantitative proteomics comparisons across diverse tissue types and states facilitate the indication of organ-specific toxicity, the identification of repurposable anticancer drug candidates and the prioritization of therapeutic targets for cancers. This study establishes a quantitative resource for navigating the proteome in the human body and in common cancers.